2010
DOI: 10.1200/jco.2008.21.3553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tamoxifen and Exemestane on Cognitive Functioning of Postmenopausal Patients With Breast Cancer: Results From the Neuropsychological Side Study of the Tamoxifen and Exemestane Adjuvant Multinational Trial

Abstract: After 1 year of adjuvant therapy, tamoxifen use is associated with statistically significant lower functioning in verbal memory and executive functioning, whereas exemestane use is not associated with statistically significant lower cognitive functioning in postmenopausal patients with BC. Our results accentuate the need to include assessments of cognitive effects of adjuvant endocrine treatment in long-term safety studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
204
2
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(222 citation statements)
references
References 38 publications
6
204
2
10
Order By: Relevance
“…Accordingly, adjuvant endocrine therapy in postmenopausal breast cancer may influence cognitive function. Tamoxifen was negatively associated with cognitive functions in some reports (Paganini-Hill & Clark 2000, Collins et al 2009) and the TEAM trial confirmed these findings by showing that tamoxifen is significantly associated with lower functioning in verbal memory and executive functioning (Schilder et al 2010). Exemestane, on the other hand, did not show significantly worse outcomes for any cognitive domain compared with healthy controls.…”
Section: Cognitionsupporting
confidence: 67%
“…Accordingly, adjuvant endocrine therapy in postmenopausal breast cancer may influence cognitive function. Tamoxifen was negatively associated with cognitive functions in some reports (Paganini-Hill & Clark 2000, Collins et al 2009) and the TEAM trial confirmed these findings by showing that tamoxifen is significantly associated with lower functioning in verbal memory and executive functioning (Schilder et al 2010). Exemestane, on the other hand, did not show significantly worse outcomes for any cognitive domain compared with healthy controls.…”
Section: Cognitionsupporting
confidence: 67%
“…The tendency seems to be that subjective ratings of memory and concentration decrease after treatment with chemotherapy, and that breast cancer patients treated with chemotherapy also seem to be more likely than controls to perceive themselves as impaired [47]. It is also unclear whether tamoxifen used for postoperative endocrine therapy has an effect on cognitive function [48,49], and the effect of aromatase inhibitors, the first option for postmenopausal breast cancer, on cognitive function is also an important issue for further study [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Mientras que en algunos trabajos se ha sugerido que el tamoxifeno s贸lo o asociado a QT puede contribuir al deterioro de la FC (34,35) , las evidencias resultan m谩s d茅biles para los inhibidores de la aromatasa (36,37) y el bloqueo androg茅nico (31,38) .…”
Section: Cambios Hormonalesunclassified